Does kinesiophobia limit physical activity and quality of life in asthmatic patients - KARACA, SEDA; POLAT, MİNE GÜLDEN; YILDIZ ÖZER, AYSEL; OĞUZ, SEMRA (My University, 2022)
Kinesiophobia has been studied in musculoskeletal and neurological diseases. The aim of this descriptive study was to assess the level of kinesiophobia in stable asthmatic patients, and to determine whether it is an obstacle to physical activity and quality of life. A total of 62 asthmatic patients and 50 healthy control subjects were assessed using the tampa kinesiophobia scale (TSK) for kinesiophobia, International Physical Activity Questionnaire-Short Form (IPAQ-SF) for physical activity levels, and Asthma Quality of Life Questionnaire (AQLQ) for quality of life. A high degree of kinesiophobia was determined in 54.8% of the asthmatic patients. The TSK scores were significantly higher (P < 0.001), and the AQLQ scores were lower in the asthma group than in the control group (P < 0.001). The IPAQ-SF level and AQLQ score were lower (P < 0.001 for both) in the asthmatic group with a high kinesiophobia score. The TSK score was significantly associated with IPAQ-SF score (r = -0.889; P < 0.001) and AQLQ score (r = -0.820; P < 0.001) in asthmatic patients. According to linear regression analysis, kinesiophobia explained 84.40% of QoL and physical activity. Patients with a stable asthma were observed to have a high level of kinesiophobia compared with healthy subjects. High kinesiophobia levels may increase the disease burden by negatively affecting participation in physical activity and quality of life. While developing asthma education programs for asthma patients, it should be remembered that even in the stable period, kinesiophobia can develop. Preventive and therapeutic programs should include precautions to improve quality of life and physical activity against the effects of kinesiophobia.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Medicine; Health Sciences; Internal Medicine Sciences; Physical Medicine and Rehabilitation; REHABİLİTASYON; Klinik Tıp; Klinik Tıp (MED); REHABILITATION; CLINICAL MEDICINE; Clinical Medicine (MED); Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation; asthma; kinesiophobia; physical activity; quality of life; ACTIVITY QUESTIONNAIRE; TAMPA SCALE; FEAR; RELIABILITY; SYMPTOMS; BARRIERS; FITNESS; IMPACT; PAIN; asthma; kinesiophobia; physical activity; quality of life